Euro area corporate debt securities market: first empirical evidence - Gabe de Bondt (European Central Bank (ECB), 2002)
A striking development in the euro area financial markets since 1999 was the rapid growth of the corporate debt securities market. This paper offers a first empirical examination of this market since the introduction of the euro using macroeconomic data. It is shown that corporate debt issuance is positively correlated with mergers and acquisitions and with industrial production, taken as a proxy of investment expenditures or working capital. Substitution with other sources of finance is shown to be related to cost differentials. The timing and size of these explanatory factors of corporate debt securities issuance differ across maturity. The empirical findings also show that corporate bond spreads lag short-term interest rates and lead real economic activity. All this suggests that the euro area corporate bond market, though still young, is informative for monetary policy and may develop into a significant link in the euro area monetary policy transmission process.
Keywords: G32; E44; 330; corporate bond spreads; Corporate debt securities issuance; euro area